2016
DOI: 10.21315/aamj2016.21.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leader-Member Exchange, Interpersonal Relationship, Individual Feeling of Energy and Creative Work Involvement Towards Turnover Intention: A Path Analysis Using Structural Equation Modeling

Abstract: To cite this article: Adil, M. S., and Awais, A. (2016). Effects of leader-member exchange, interpersonal relationship, individual feeling of energy and creative work involvement towards turnover intention: A path analysis using structural equation modeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 107 publications
(124 reference statements)
1
23
2
2
Order By: Relevance
“…In particular, the results did not indicate a direct path between interpersonal conflict and turnover intention. However, because several previous studies have reported a direct relationship between interpersonal conflict and turnover intention [98,99], further research using various samples will be required to verify our results so that generalizations can be made.…”
Section: Discussionmentioning
confidence: 75%
“…In particular, the results did not indicate a direct path between interpersonal conflict and turnover intention. However, because several previous studies have reported a direct relationship between interpersonal conflict and turnover intention [98,99], further research using various samples will be required to verify our results so that generalizations can be made.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, previous authors have studied LMX relationship in relation with different organizational variables e.g., affective commitment (Imran & Fatima, 2013), organizational citizenship behavior (Imran & Fatima, 2013;Ishaq, Munazer, Hussain, Asim, & Cheema, 2012;Nazir, Aslam, & Nawaz, 2011;Shaukat, Senin, & Ahmed, 2012), intention to leave (Adil & Awais, 2016;Imran & Fatima, 2013), perceived organizational support (Ismail, Journal of Management Sciences Jafri, & Khurram, 2011;Shaukat et al, 2012), job satisfaction (Shaukat et al, 2012), distributive justice (Nazir et al, 2011), self-esteem (Ismail et al, 2011), task and contextual performance (Saboor, Mukhtar, & Sadiq, 2015), and procedural justice (Ishaq et al, 2012).…”
Section: Leader-member Exchange (Lmx) Theorymentioning
confidence: 99%
“…Some previous studies were unable to find a correlation between LMX and employee turnover intent (Schyns, Torka, & Gossling, 2007;Vecchio & Norris, 1996;Vecchio, 1985). However, other previous studies found that LMX is negatively related to employee turnover intent (Adil & Awais, 2016;Abu Elanain, 2014;Saeed, Waseem, Sikander, & Rizman, 2014;Joo, 2010). As a result, there are inconsistencies in previous studies regarding the relationship between LMX and employee turnover intent.…”
Section: Introductionmentioning
confidence: 94%